Cost-effectiveness of population-based screening for chronic obstructive pulmonary disease in China: a simulation modeling study - Chen, Qiushi; Fan, Yiwen; Huang, Ke; Li, Wei; Geldsetzer, Pascal; Bärnighausen, Till; Yang, Ting; Wang, Chen; Chen, Simiao (The lancet. Regional Health. Western Pacific, 2024)
Background - China has the highest disease burden of chronic obstructive pulmonary disease (COPD) in the world; however, the diagnosis rate remains low. Screening for COPD in the population may improve early diagnosis and long-term health outcomes for patients with COPD. In this study, we aimed to evaluate the cost-effectiveness of population-based COPD screening policies in China. - Methods - We developed a microsimulation model that simulated incidence, natural history, and clinical management of COPD over a lifetime horizon among the general population aged 35-80 years in China. We evaluated population-based screening policies with different screening methods (one-step with COPD Screening Questionnaire or two-step with additional portable spirometer test) and frequencies (one-time or every 1-10 years). We calculated the incremental cost-effectiveness ratio (ICER) of the screening policies compared with the status quo (without screening) and identified the most cost-effective screening policy. Scenario and sensitivity analyses were performed to assess the impact of key parameters and the robustness of model results. - Findings - Compared with the status quo, all population-based COPD screening policies were cost-effective with estimated ICERs ranging between $8034 and $13,209 per quality-adjusted-life-year (QALY), all under the willingness-to-pay value of $38,441/QALY (three times China's gross domestic product per capita). A total of 0.39%-8.10% of COPD-related deaths and 0.58%-2.70% of COPD exacerbations were projected to be averted by COPD screening. Among all screening policies, annual two-step screening was the most cost-effective. Improving the linkage from screening to diagnosis and treatment could further increase population health benefits and the cost-effectiveness of COPD screening. - Interpretation - Population-based screening for COPD could be cost-effective in China. Offering public programs for COPD screening similar to existing preventive health services for other chronic diseases could be a promising strategy to improve population health outcomes and mitigate the disease burden of COPD in China. - Funding - Alexander von Humboldt Foundation, National Natural Science Foundation of China, CAMS Innovation Fund for Medical Science, Chinese Academy of Engineering project, and Horizon Europe.
Gesehen am 28.01.2025